The Impact of Credit Watch and Bond Rating Changes on Abnormal Stock Returns for Non-USA Domiciled Corporations - EE, Benjamin Boon Ching (Institutional Knowledge at Singapore Management University, 2008)
In this paper, we investigate whether credit watches and bond rating changes issued by Moodys' and S&P Credit Rating Agencies provide significant new information to investors for Non-USA domiciled corporations. We also examine whether the stock related cumulative abnormal return (CAR) differs according to the classification of the country of domicile (emerging or developed) of the corporation, and varies by state of the local stock market during the time of the rating event.We find that on average, negative credit watches as well as long term rating downgrades result in significant stock related CAR for Non-USA domiciled 4 corporations. However, positive credit watches and long term rating upgrades generally do not result in significant stock related CAR. On average, we find that negative credit watches result in a stock related CAR of -1.37% within the (-1, +1) window centered around the watch issuance, while long term rating downgrades result in a stock related CAR of -1.33% within the (-1, +1) window centered around the downgrade. Developed markets generally exhibit a stronger reaction. Negative watch in developed markets have a stock related CAR of -1.44%, compared to only -0.88% for emerging markets. The picture is similar for long term rating downgrades. Downgrades in developed markets have a stock related CAR of -1.47%, compared to only -0.76% for emerging markets. This paper provides evidence that credit rating agencies are able to provide new information to investors outside of companies domiciled in the USA.